Use of Intensive Soil Working Technique in Afforestation of Wastelands - Singh, V. R. (Indian Forester, 1991)
The degraded forest wastelands are prone to heavy grazing and are consequently eroded and compact. Therefore, 90% of rain water runs away leaving very little portion of it to percolate into sub-soil. By traditional pit planting method only about 20.25 m3 rain water can be harvested per ha at given time. This is highly Inadequate. In order to harvest maximum precipitation by percolation there is need to carry out intensive soil working. The method suggested here deals with technique of water retention through ploughing and digging of ’V’ shape furrows intercepted by small bunds at 2 metres intervals. By this technique 1500 m3 of rain water can be barvested per bectare at a time. The technique is very relevant to plain areas of low rain fall and hlgb temperature zones, partIcularly the drought prone areas of Maharasblra State. The cost per ha works out to same when compared with the traditional method of pit planting. The ploughing is done prior to seeding of existing poor quality grasses which results into its eradication to a great extent. Besides, decomposition of grasses into soil ensure better humus formation.